Inovação incremental em processos: a experiência da Universidade Federal do Tocantins no uso/manejo do Sistema UFT DOCS - Barros , Samuel Lima Gomes de (Universidade Federal do Tocantins, 2024)
This study aimed to present an incremental innovation using an Application Programming Interface (API) in the access authorization process for the use of the UFT Docs platform, used by the Federal University of Tocantins to manage and provide institutional and academic documents to the community. Methodologically, to delimit the theme, establish objectives and formulate a hypothesis, the work used exploratory research combined with a bibliographic research for the theoretical basis. A digital field research was carried out on 63 websites of federal higher education institutions, which provided data for the qualitative and quantitative research of the work; finally, a case study was carried out at UFT regarding the systems used to provide documents to the public. The results showed that UFT is aligned in almost all the evaluated aspects with the majority of the surveyed institutions, except for the way the access management to the publication system is done, which in the Tocantins institution is the responsibility of the Communication sector. In this sector, the process still occurs with requests sent by email, which ends up generating unnecessary time gaps in relation to the authorization process for using the tool, directly impacting the necessary speed for certain documents, such as public notices. The study brought as a result the proposal of an incremental change in the flowchart of the authorization to use the UFT Docs tool, using an API fed with data from Siape (a government system that provides data on public servants and can be accessed without human interference) instead of the demands made by email to a sector other than the Information Technology sector. The proposed change will have a significant impact on the speed of responses, the security of systems directly fed with government data, the decentralization of authorizations for access to the publication platform, and, in addition to this, the availability of PDF and video manuals will help in the fixation of the necessary norms for the process, also contributing to the documentary standard of UFT.